Supramolecular Aggregates of Amide‐ and Urea‐Functionalized Nanographene - Haruka Moriguchi; Ryo Sekiya; Takeharu Haino (ChemistryEurope)
Controlling the morphology of supramolecular nanographene (NG) aggregates is challenging. This study confirms that amide‐ and urea‐functionalized NG undergo self‐assembly to form supramolecular aggregates with a morphology that depends on the incorporated functional group. Amide‐functionalized NG forms stacked aggregates, whereas urea‐functionalized NG organizes into network polymers. These distinct morphologies suggest that amide groups drive NG stacking, whereas urea groups support NG vertically and horizontally, likely owing to differences in the strengths of single and bifurcated NH/O hydrogen bonds. Moreover, the functional group incorporated into NG influences the gelation properties of the system. Among the two tested systems, only urea‐functionalized NG formed organogels, possibly because urea–urea hydrogen bonds, enable solvent‐molecule trapping inside the network polymers formed in these NG systems. Thus, hydrogen bonds can regulate the morphology and function of supramolecular NG aggregates.